Instagram Media Management in Building Government Image at West Aceh Diskominsa - Ramadhani, Ramadhani; Fadhlain, Said; Muzakkir, Muzakkir (Malikussaleh Social and Political Reviews, 2024)
The development of technology today helps humans in doing activities and getting information. Technology has been present and become part of the life of modern society, one of the results of technological advances is the emergence of social media such as Instagram. Currently, Instagram is not only used by someone personally, but government agencies also use social media as a means of conveying information and building an image to the public. This study aims to determine how the management of Instagram social media @diskominsa_acehbarat in building the government's image. This research uses descriptive qualitative research methods with data collection techniques through interviews, observation, and documentation. The results of this study found that the management of the account was carried out through four stages, namely: (1) reporting; (2) news preparation; (3) editing; (4) uploading news to Instagram social media @diskominsa_acehbarat. Although in this management there are obstacles, management is still carried out in order to build a good government image